Structure based design of effective HtpG-derived vaccine antigens against M. tuberculosis - Ruggiero, Alessia; Choi, Han-Gyu; Barra, Giovanni; Squeglia, Flavia; Back, Young Woo; Kim, Hwa-Jung; Berisio, Rita (Frontiers in Molecular Biosciences, 2022)
Vaccine development against Tuberculosis is a strong need, given the low efficacy of the sole vaccine hitherto used, the Bacillus Calmette–Guérin (BCG) vaccine. The chaperone-like protein HtpGMtb of M. tuberculosis is a large dimeric and multi-domain protein with promising antigenic properties. We here used biophysical and biochemical studies to improve our understanding of the structural basis of HtpGMtb functional role and immunogenicity, a precious information to engineer improved antigens. We showed that HtpGMtb is a nucleotide-binding protein identify the dimerisation interface on the C-terminal domain of the protein. We also showed that the most immunoreactive regions of the molecule are located on the C-terminal and middle domains of the protein, whereas no role is played by the catalytic N-terminal domain in the elicitation of the immune response. Based on these observations, we experimentally validated our predictions in mice, using a plethora of immunological assays. As an outcome, we designed and developed vaccine antigens with enhanced biophysical properties and ease of production, albeit conserved or enhanced antigenic properties. Our results prove the efficacy of structural vaccinology approaches in improving our understanding of the structural basis of immunogenicity, a precious information to engineer more stable, homogeneous, efficiently produced, and effective vaccine antigens.